2015
DOI: 10.1111/gcbb.12255
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy harvest, climate change, and forest carbon in the Oregon Coast Range

Abstract: Forests provide important ecological, economic, and social services, and recent interest has emerged in the potential for using residue from timber harvest as a source of renewable woody bioenergy. The long-term consequences of such intensive harvest are unclear, particularly as forests face novel climatic conditions over the next century. We used a simulation model to project the long-term effects of management and climate change on above-and belowground forest carbon storage in a watershed in northwestern Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
1
14
1
Order By: Relevance
“…Boisvenue and Running, 2010), but are in contrast to other studies that do not show this pattern (e.g. Creutzburg et al, 2016). Carbon stocks tended to follow changes in productivity, increasing in ecoregions with greater productivity and decreasing where productivity was projected to fall, indicating a lower influence of changing decay rates on the stocks over this simulation period.…”
Section: Climate Change Effects On Carbon Fluxes and Stockscontrasting
confidence: 99%
“…Boisvenue and Running, 2010), but are in contrast to other studies that do not show this pattern (e.g. Creutzburg et al, 2016). Carbon stocks tended to follow changes in productivity, increasing in ecoregions with greater productivity and decreasing where productivity was projected to fall, indicating a lower influence of changing decay rates on the stocks over this simulation period.…”
Section: Climate Change Effects On Carbon Fluxes and Stockscontrasting
confidence: 99%
“…Although there is some debate about the expected effects of increasing temperature on soil C stocks (Davidson and Janssen 2006, Schmidt et al 2011, Bellassen and Luyssaert 2014, our results are consistent with a meta-analysis that found an increase in both soil respiration and plant productivity with warming (Rustad et al 2001). Another related study in a single watershed within the Coast Range found a relatively small decrease in aboveground, soil and detrital C due to climate change (Creutzburg et al 2015). The current study expanded to a broader region with greater overall precipitation (and thus lower summer water limitation), and incorporated improvements to the modeled soil water algorithms.…”
Section: Climate Change Impactssupporting
confidence: 89%
“…Another related study in a single watershed within the Coast Range found a relatively small decrease in aboveground, soil and detrital C due to climate change (Creutzburg et al. ). The current study expanded to a broader region with greater overall precipitation (and thus lower summer water limitation), and incorporated improvements to the modeled soil water algorithms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Forest succession.-We obtained model parameters from the literature and available datasets including the USDA Fire Effects Information System (Abrahamson; https://www.feis-crs.org/feis/), USGS Vegetation Atlas of North America (Thompson et al 1999; https://pubs.usgs.gov/pp/ p1650-a/), the Northeastern Ecosystem Research Cooperative's Foliar Chemistry Database (NERC 2015; http://www.nercscience.org/), the National Atmospheric Deposition Program (NADP 2015; http://nadp.slh.wisc.edu/data/ntn/), the Oak Ridge National Laboratory database (West 2014; https://daac.ornl.gov/SOILS/guides/West_Soil_Carb on.html), and from previous studies that utilized LANDIS-II species parameterization (Loudermilk et al 2014, Lucash et al 2014, Creutzburg et al 2016.…”
Section: Model Parameterization and Validationmentioning
confidence: 99%